2019
DOI: 10.1038/s41418-019-0453-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor ZHX2 inhibits NAFLD–HCC progression via blocking LPL-mediated lipid uptake

Abstract: Non-alcoholic fatty liver disease (NAFLD) leads to hepatocellular carcinoma (HCC). However, the underlying mechanism remains largely unclear. Here, we investigated the role of the tumor suppressor Zinc fingers and homeoboxes 2 (ZHX2) in the progression of NAFLD to HCC. ZHX2 expression was significantly decreased in fatty liver tissues, especially in the liver with NAFLD-HCC. ZHX2 overexpression disturbed lipid homeostasis of cultured HCC cells, and inhibited lipid deposition in hepatocytes both in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…ZHX2 not only inhibits transcription of AFP and GPC3 in HCC [19][20][21] but also down-regulates cyclin A and cyclin E to reduce cell proliferation, and MDR1 to enhance the chemo-sensitivity of HCC [21,22]. Together with other data, our data suggest lipid reprograming as a new mechanism for ZHX2-mediated HCC suppression [15,16,24]. A recent study showed that a…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…ZHX2 not only inhibits transcription of AFP and GPC3 in HCC [19][20][21] but also down-regulates cyclin A and cyclin E to reduce cell proliferation, and MDR1 to enhance the chemo-sensitivity of HCC [21,22]. Together with other data, our data suggest lipid reprograming as a new mechanism for ZHX2-mediated HCC suppression [15,16,24]. A recent study showed that a…”
Section: Discussionsupporting
confidence: 75%
“…This result indicated that ZHX2 plays an important role in the development of NAFLD, which is an independent risk factor for HCC [3–5]. Similarly, our recent research showed that ZHX2 transcriptionally repressed expression of LPL, led to a decrease of exogenous lipid uptake, and retarded the progression of NAFLD‐HCC [15]. In addition to exogenous lipids, DNL was increased in many tumor biological processes, including promoting cell proliferation and metastasis, and enhancing chemoresistance [8,9,33].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Yue et al 27 also discovered that ZHX2 inhibited the growth of HCC cell lines by transcriptional represses of two key cell cycle regulators, Cyclin A and Cyclin E 27 . Later, Wu et al 28 reported ZHX2 could protect hepatocytes from lipid deposition disorder in non-alcoholic fatty liver disease to retard cell growth and its-related HCC progression. All these researches illustrated that in the process of disease and tumorigenesis, ZHX2 usually played the role of tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%